URGENSI PERUBAHAN PENGATURAN SYARAT PENGANGKATAN NOTARIS UNTUK MEWUJUDKAN PROFESIONALISME JABATAN NOTARIS DI INDONESIA - Aldi, Aldi (Tanjungpura Acta Borneo Jurnal, 2024)
Abstract  Notary is a public official who is authorized to make authentic deeds and has other authorities as referred to in the Notary Position Law or based on other laws. To create notaries who have extensive skills and knowledge, a strict selection is needed to become a notary, currently the Notary Position Law has not really regulated the latest requirements in accordance with current developments, when there is a Minister of Law and Human Rights Regulation related to the requirements for the appointment of notaries, it is always canceled because it conflicts with the Notary Position Law. The purpose of this study is to determine and analyze the Urgency of Changes in the Regulation of Notary Appointment Requirements to Realize the Professionalism of the Notary Position in Indonesia.The method used is Normative Legal Research, with the nature of the research, namely Descriptive analytical, research sources in the form of primary legal materials and secondary legal materials and non-law materials or so-called tertiary legal materials, using Primary and Secondary Legal Material Collection Techniques, and Direct Communication Techniques by interviewing related parties.  Based on the results of the research conducted by the author, the Notary Appointment in the Notary Position Law is currently irrelevant, due to the reality that occurs in the field today, including many public reports on Notary Problems, the large number of Kenotariatan master graduates who want to become Notaries, and the incompatibility of the rules in the Notary Position Law so as to provide a Negative view that the current requirements that are not regulated by law as a place to seek fees and business solely and are outlined in the association regulations are legalized and binding and force to all prospective notaries and extraordinary members. The purpose of the presence of the Minister of Law and Human Rights Regulation is to regulate the terms of appointment of Notaries to strive to improve the quality of Notaries in providing excellent, fast, effective and efficient services to the public, it is necessary to prepare Notaries with quality and integrity but are always canceled so that it is hoped that changes in the terms of appointment in the Notary Office Law and give the Minister of Law and Human Rights the authority to regulate the terms of appointment according to needs, so that the terms of appointment of Notaries can create justice, certainty, and legal benefits for prospective Notaries and to realize the Professionalism of the Notary OAbstrakNotaris merupakan Pejabat umum yang berwenang untuk membuat akta autentik dan memiliki kewenangan lainnya sebagaimana dimaksud dalam Undang-Undang Jabatan Notaris atau berdasarkan undang-undang lainnya. Untuk menciptakan notaris yang mempunyai skill dan pengetahuan yang luas, dibutuhkan seleksi yang ketat untuk menjadi notaris, saat ini Undang-Undang Jabatan Notaris belum terlalu mengatur syarat terbaru sesuai dengan perkembangan saat ini, pada saat adanya Peraturan menteri Hukum dan Hak Asasi Manusia terkait syarat untuk pengangkatan notaris, selalu dibatalkan karena bertentangan dengan Undang-Undang Jabatan Notaris. Tujuan penelitian ini untuk mengetahui dan menganalisis Urgensi Perubahan pengaturan Syarat Pengangkatan Notaris untuk Mewujudkan Profesionalisme Jabatan Notaris di IndonesiaMetode yang digunakan adalah Penelitian Hukum Normatif, dengan Sifat penelitian yaitu Deskriptif analitis, sumber-sumber penelitian yang berupa bahan-bahan hukum primer dan bahan-bahan hukum sekunder dan bahan non hukum atau yang disebut bahan hukum tersier, menggunakan Teknik Pengumpulan Bahan Hukum Primer dan Sekunder, dan Teknik Komunikasi Langsung dengan mewawancarai pihak terkait.  Berdasarkan hasil penelitian yang penulis lakukan, Pengangkatan Notaris dalam Undang-Undang Jabatan Notaris saat ini sudah tidak relevan, dikarenakan Realita yang terjadi dilapangan saat ini diantaranva banyak laporan masyarakat terhadap Permasalahan Notaris, banyak nya lulusan magister Kenotariatan yang ingin menjadi Notaris, serta tidak sesuai nya aturan yang ada di Undang-Undang Jabatan Notaris sehingga   memberikan pandangan Negatif bahwa syarat yang ada saat ini yang tidak diatur oleh undang-undang sebagai tempat untuk mencari biaya dan bisnis semata-mata dan dituangkan dalam peraturan perkumpulan dilegalkan dan mengikat dan memaksa kepada seluruh calon notaris dan anggota luar biasa. Tujuan Kehadiran Peraturan Menteri Hukum dan HAM membuat regulasi syarat pengangkatan Notaris untuk mengupayakan meningkatkan kualitas Notaris dalam memberikan pelayanan prima, cepat, efektif dan efisien kepada masyarakat, perlu mempersiapkan Notaris yang berkualitas dan berintegritas   tetapi selalu dibatalkan sehingga diharapkan perubahan syarat pengangkatan di Undang-Undang Jabatan Notaris dan memberikan kewenangan kepada Menteri Hukum dan Ham memubat regulasi syarat pengangakatan sesuai dengan kebutuhan, agar syarat pengangkatan Notaris bisa menciptakan keadilan, Kepastian, dan kemanfaatan Hukum bagi calon Notaris serta untuk Mewujudkan Profesionalisme Jabatan Notaris di Indonesiaffice in Indonesia.